2006
DOI: 10.1016/j.jcis.2005.09.028
|View full text |Cite
|
Sign up to set email alerts
|

AFM and low-pressure argon adsorption analysis of geometrical properties of phyllosilicates

Abstract: The distribution of edge and basal surface areas of phyllosilicate particles is an essential parameter for understanding the interaction mechanisms at solid/gas or solid/liquid interfaces. Among the techniques proposed to determine the geometrical heterogeneities of flat solids, low-pressure argon adsorption and AFM analysis are the most promising to derive the weight-averaged values of specific surface areas. A series of publications have recently been dedicated to the combination of both methods showing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…However, the edge surface area (ESA) estimated from DIS was 55.4 m 2 g À1 (SSA domain 1 + SSA domain 2), which is a factor of 5 higher than that estimated by AFM observations (11.2 m 2 g À1 ). This result differs from the values obtained for the purified (i.e., natural) montmorillonite and other clays (Sayed Hassan et al, 2006). Table 3 lists the steady-state experimental results (whole data set of experimental results is available in Supplementary Electronic Appendix A).…”
Section: Low-pressure Gas Adsorption Resultsmentioning
confidence: 69%
“…However, the edge surface area (ESA) estimated from DIS was 55.4 m 2 g À1 (SSA domain 1 + SSA domain 2), which is a factor of 5 higher than that estimated by AFM observations (11.2 m 2 g À1 ). This result differs from the values obtained for the purified (i.e., natural) montmorillonite and other clays (Sayed Hassan et al, 2006). Table 3 lists the steady-state experimental results (whole data set of experimental results is available in Supplementary Electronic Appendix A).…”
Section: Low-pressure Gas Adsorption Resultsmentioning
confidence: 69%
“…As typical for phyllosilicates (Sayed Hassan et al, 2006;Villiéras et al, 1992Villiéras et al, , 1997aVilliéras et al, , 1997b, the derivative isotherms exhibited a peak at ln(P/P 0 ) near À4 to À5, and a shoulder and a tail at greater energy (i.e. at lower values of ln(P/P 0 )).…”
Section: Resultsmentioning
confidence: 75%
“…The validity of this method was first tested on kaolinite and sepiolite via comparison of results obtained with those from low-temperature adsorption microcalorimetry (Villiéras et al, 1992(Villiéras et al, , 1997a. More recently, the study of the geometric properties of smectite, kaolinite, and illite using both AFM and argon adsorption (Tournassat et al, 2003, Sayed Hassan et al, 2006 demonstrated the consistency between these two methods. Argon adsorption has also been used to study the shape and size of smectite particles, including saponite , montmorillonite, and nontronite (Tournassat et al, 2003;Peronnet et al, 2007;Le Forestier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smectites are characterized by their high permanent surface charge density, very high specific surface area, and also by their elongated form compared to kaolinites (Hassan et al, 2006;Leroy and Revil, 2009;. As explained by Lockhart (1980) and Tombacz and Szekeres (2004), a smectite aggregate resembles a honeycomb of closed edge-to-face, edge-to-edge, and face-toface units, whereas kaolinite tactoids are stacked as face-to-face units (Hassan et al, 2006;Leroy and Revil, 2009;Tombacz and Szekeres, 2006). Therefore, the distribution of relaxation times associated with the electrochemical polarization of the Stern layers around smectite particles is broader than that of the kaolinite particles.…”
Section: Comparison Between the Experimental Data And The Modelmentioning
confidence: 99%